THE PARTNER’S PRESENCE IN DELIVERY CARE: THE PROFESSIONALS´ EXPERIENCE - Komura Hoga, Luiza Akiko; de Souza Pinto, Cleusa Maia (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The W.H.O. recommends the partner’s presence during childbirth. Objective: To describe professional staff experiences related to the partner’s presence during childbirth. Methodology: Research was carried in a hospital in the state of Sao Paulo, Brazil, between January and June 2001. Twenty four professionals (obstetricians, neonatologists, midwifery nurses and ancillary nurses) were interviewed. Findings: The presence of the partner provoked positive reﬂexes on several aspects of childbirth care. The partner’s inclusion in childbirth requires systematic preparation and should be framed in an integral project of care humanization. The professionals identiﬁed other demands following the partner’s involvement in childbirth care. Conclusions: The institution and the professionals require previous preparation when partners will take part in childbirth care as part of an integral childbirth care humanization proposal